2014
DOI: 10.2217/pgs.14.99
|View full text |Cite
|
Sign up to set email alerts
|

ABCC3 and OCT1 Genotypes Influence Pharmacokinetics of Morphine in Children

Abstract: Aim Large interindividual variability in morphine pharmacokinetics could contribute to variability in morphine analgesia and adverse events. Methods Influence of weight, genetic polymorphisms, race and sex on morphine clearance and metabolite formation from 220 children undergoing outpatient adenotonsillectomy was studied. A nonlinear mixed effects model was developed in NONMEM to describe morphine and morphine glucuronide pharmacokinetics. Results Children with ABCC3 −211C>T polymorphism C/C genotype had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 47 publications
(53 reference statements)
2
56
0
Order By: Relevance
“…Studies assessing whether these findings apply to pain phenotypes in different pediatric age ranges are needed, as well as studies on the clinical consequence of SLC22A1 genetic variability in the pediatric population. Sufficient evidence on tramadol and morphine PK with SLC22A1 genetics has been found in adult and pediatric populations, with all studies replicating and confirming previous findings (39,42,44,47 ).…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Studies assessing whether these findings apply to pain phenotypes in different pediatric age ranges are needed, as well as studies on the clinical consequence of SLC22A1 genetic variability in the pediatric population. Sufficient evidence on tramadol and morphine PK with SLC22A1 genetics has been found in adult and pediatric populations, with all studies replicating and confirming previous findings (39,42,44,47 ).…”
Section: Discussionsupporting
confidence: 73%
“…In a study with 103 adult white individuals, 51 genetic variations were discovered, but only the promoter SNP Ϫ211CϾT (rs4793665) was associated with significantly decreased ABCC3 mRNA expression and alterations in the binding of transcription factors (38 ). A study with 105 children undergoing adenotonsillectomy indicated that the Ϫ211CϾT polymorphism was associated with lower M3G and M6G plasma concentrations (39 ). All 12 patients with undetectable M6G concentrations were carriers of the T-allele, which is in line with in vitro data from Lang et al (38 ).…”
Section: Abcc3mentioning
confidence: 99%
See 1 more Smart Citation
“…We earlier studied formation of morphine metabolites, morphine-6-glucuronide and morphine-3-glucuronide along with morphine clearance [11]. The OCT1 homozygotes had lower morphine clearance and reduced metabolite formation (∼39%).…”
Section: Discussionmentioning
confidence: 99%
“…The efflux of morphine glucuronides from the hepatic cell is an ATP-dependent process mediated by the ATP-binding cassette transporters including ABCC3 [9,10]. We recently demonstrated that ABCC3 variants contribute to variability in morphine, morphine-3-glucuronide and morphine-6-glucuronide pharmacokinetics (PK) and clinical outcomes [11,12].…”
Section: Future Science Groupmentioning
confidence: 99%